The Atlas of Siberia by S. U. Remezov as a source of initial period of ethnographical studies of Tuvans - Irgit, Choduraa K. (The New Research of Tuva, 2014)
The article deals with the "Atlas of Siberia” by S.U. Remezov (1701) which is one of the most significant cartographical sources of the initial period of ethnographical studies of Tuvans.
Keywords: Tuvans’ ethnography; periodization; cartographical source; ethnographical tuvinology